Análise técnico-econômica da recuperação de um solo sódico no peímetro irrigado curu-pentecoste-CE. - Aragão, Ana Paula Bezerra (2009)
In the semi-arid part of Northeastern Brazil, the highest incidences of salinized areas are observed in land subjected to intense irrigated cultivation, in the “Perímetros Irrigados” (irrigated perimeters), particularly those where is used the surface method. The experiment was performed in the “Núcleo D” (D Core) of the “Perímetro Irrigado Curu-Pentecoste - Ce”. The research aimed at evaluating the effect of the subsoiling of the treated area combined with the application of chemical and biological treatments in the same area. Specifically, it aimed at evaluating the effect of the said combination (a) in the improvement of the hydraulic properties in the profile of the soil, (b) in the improvement of the productivity of the cowpea [Vigna unguiculata (L.) Walp.] of the Epace 11 cultivar and (c) in the indicators of profitability of the recovery of a sodic soil irrigated by furrows. We used a randomized complete block experimental design with five treatments and five replications. The treatments were T0: control, T1: 40 t ha-1 of organic matter, T2: 20 t ha-1 gypsum T3: 20 t ha-1 (gypsum) + 40 t ha-1 (MO) T4: 10 t ha-1 (gypsum) + 20 t ha-1 (MO). The results allowed the following conclusions: 1) The grain yield with the use of chemical enhancers was 120% higher than the productivity without those enhancers and 18% lower than the productivity (of the same cultivation) in soils without salinity problems. 2) The highest bean yields are associated with the largest values of water table depth, the increase in grain yield with the depth of the water table occurring at a rate increasing with the same depth. 3) The application of 20 t ha-1 gypsum and 40 t ha-1 Organic matter, no later than in the first year, reduced the percentage of exchangeable sodium in the soil, from an initial average above 50% to a convergent value of 2%. 4) The limitation on the elevation of the outflow of lateral drains indicate the necessity of the installation of an underground drainage system of the interception type, even if the average hydraulic gradient of the of groundwater flow is well below 1%. 5) The rate between the gross value of production generated by the cowpea crop and the cost of remediation of soil, shows that the the crop contributes with 12% of the cost of soil sodium remediation . 6) The recovery process shows a good feasibility at a rate of 12% per year and high viability at a rate of interest of 6% per year, revealing that at that rate all the investment will be recovered and paid, plus yelding an extra profit of R$ 5,328.85.